2023
DOI: 10.1186/s12884-023-05622-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of caesarean section deliveries in the Kintampo Districts of Ghana

Abstract: Background Globally, the increasing rate of caesarean section (CS) delivery has become a major public health concern due to its cost, maternal, neonatal, and perinatal risks. In Ghana, the Family Health Division of the Ghana Health Service in 2016 opted to initiate a program to prevent the abuse of CS and identify the factors contributing to its increase in the country. This study aimed to determine the prevalence and factors influencing CS deliveries in the Kintampo Districts of Ghana. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Accordingly, the study showed that the prevalence of caesarean section was 28.70%. This is higher than previous studies conducted in Ghana in public health facilities which varies across the various regions [11][12][13][14]26]. The prevalence is higher than the recommended rate of 10-15 percent [6].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Accordingly, the study showed that the prevalence of caesarean section was 28.70%. This is higher than previous studies conducted in Ghana in public health facilities which varies across the various regions [11][12][13][14]26]. The prevalence is higher than the recommended rate of 10-15 percent [6].…”
Section: Discussionmentioning
confidence: 67%
“…Like other African countries, the incidence of CS in Ghana varies across according to the level of healthcare rates of 14%, 18.5% and 26.9% [11][12][13][14]. CS utilization has both positive and negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important consideration in family planning. 22 4. Post-Surgery Mental Health: Some mothers experience a psychological impact after a Caesarean section, especially if the operation was not planned beforehand.…”
Section: Health Implications Of Caesarean Sectionmentioning
confidence: 99%
“… 1 Although CD is becoming increasingly popular, its rising cost and maternal, neonatal, and perinatal risks have caused a significant public health concern. 2 According to the World Health Organization, CD rates have increased from 7% in 1990 to 21% today. 3 There is an estimation that by 2030 the global average CD rate will increase to 28.5%, with more than 38 million births by CD.…”
Section: Introductionmentioning
confidence: 99%